2017
DOI: 10.3390/nu9030263
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective Effects of Ginsenoside Rg1 in  Human Osteoarthritis Chondrocytes and a Rat Model  of Anterior Cruciate Ligament Transection

Abstract: This study aimed to assess whether Ginsenoside Rg1 (Rg1) inhibits inflammatory responses in human chondrocytes and reduces articular cartilage damage in a rat model of osteoarthritis (OA). Gene expression and protein levels of type II collagen, aggrecan, matrix metalloproteinase (MMP)-13 and cyclooxygenase-2 (COX-2) were determined in vitro by quantitative real-time-polymerase chain reaction and Western blotting. Prostaglandin E2 (PGE2) amounts in the culture medium were determined by enzyme-linked immunosorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
(41 reference statements)
1
36
0
Order By: Relevance
“…In present studies, the doses of Rg1 usually ranged from 10 to 40 mg/kg in animal models, and 10 to 40 μM in cells [ 16 , 17 , 21 , 23 , 42 , 47 ]. In this work, we investigated the effect of Rg1 at doses of 10 and 20 mg/kg in an animal, and found that both doses could ameliorate HFD-induced obesity, but the effect of 20 mg/kg Rg1 was more significant than 10 mg/kg.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In present studies, the doses of Rg1 usually ranged from 10 to 40 mg/kg in animal models, and 10 to 40 μM in cells [ 16 , 17 , 21 , 23 , 42 , 47 ]. In this work, we investigated the effect of Rg1 at doses of 10 and 20 mg/kg in an animal, and found that both doses could ameliorate HFD-induced obesity, but the effect of 20 mg/kg Rg1 was more significant than 10 mg/kg.…”
Section: Discussionmentioning
confidence: 93%
“…Rg1 exists both in Panax ginseng and Panax quinquefoliu , and is especially abundant in the leaves of Panax quinquefoliu [ 9 , 17 , 18 , 19 , 20 ]. It has been found that Rg1 can reduce oxidative damage in liver as antioxidants, promote the capability of learning and memory, and can also be used to prevent cardiovascular diseases and diabetes [ 16 , 17 , 21 , 22 ]. Additionally, it was shown that Rg1 increased plasma membrane translocation of GLUT4 in C2C12 skeletal muscle cells, and protected mice from dietary-induced obesity via activation of the AMPK pathway [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al investigated the chondroprotective effects of ginsenoside Rg1 (G-Rg1) in human OA patients and an OA rat model by preparing articular chondrocytes from OA patients and an OA rat model that underwent ACLT. Histological analyses showed that G-Rg1 suppressed gene and protein expression of MMP-13, COX-2, and prostaglandin E 2 and prevented the degradation of COLII and aggrecan in IL-1β–stimulated human OA articular chondrocytes [56]. G-Rg1 also ameliorated OA symptoms in ACLT OA rats by attenuating cartilage degradation and decreasing COLII loss and MMP-13 level [56].…”
Section: Effects Of Ginseng and Ginsenosides In Rheumatic Diseasesmentioning
confidence: 99%
“…Saponin is a kind of bioactive substance with a range of physiological functions, such as anti-inflammatory, anti-cancer, immunoregulatory and anti-fatigue effects [ 14 , 15 ]. Various saponins have disparate physiological activities as a result of diverse skeletons and sugar moieties.…”
Section: Introductionmentioning
confidence: 99%